TUJUAN GURU TUNGGAL MELAKSANAKAN PEMBELAJARAN DI TAMAN PENDIDIKAN AL-QUR’AN TABA MUTUNG KABUPATEN BENGKULU TENGAH - Sri Wahyuni; Rufran Zulkarnain; Parlan Parlan (Jurnal Pendidikan Sepanjang Hayat, 2020)
This research is a descriptive qualitative study which aims to describe the objectives of a single teacher in implementing learning in Al-Qu'an Education Park. Participants in this study were the Village Head, Pupils, and Guardian Students. This research was conducted at the Al-Qur'an Taba Mutung Education Park, Central Bengkulu Regency on March 7 - May 19 2020 .Data collection was carried out through interviews,observation and documentation. Data were analyzed and validated using triangulation data validity techniques. From the results of the research, the aim of a single teacher to carry out learning in the Al-Qu'an Education Park is so that the community, especially the children of the Qur'ani generation, is a generation that is committed to the Al-Qur'an as a source of behavior, a basis for life and a reference for all its affairs. Keywords: Learning objectives, Al-Qur'an Education Park.